Profitabilitas, Capital Intensity, Dan Tax Advoidance: Komite Audit Sebagai Pemediasi (Study Empiris Perusahaan Manufaktur Periode 2018-2021) - Sapurang Sangadji (Yayasan Literasi Ilmiah Indonesia, 2022)
Purpose: this study aims to obtain empirical evidence of the influence of profitability, capital intensity and tax avoidance of audit committees as mediates. Method: The data used in this study is secondary data obtained from manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2018 – 2021. This research uses multiple linear regression analysis and the Sobel test method. Findings: The results of this study indicate that profitability has a positive effect on audit committees, capital intensity has a positive effect on audit committees, audit committees have no positive effect on tax avoidance, profitability has a negative effect on tax avoidance, capital intensity has a positive effect on tax avoidance, profitability has a positive effect on tax avoidance through the audit committee, capital intensity has no positive effect on tax avoidance through the audit committ Novelty: The novelty of this research uses a different research method by using the audit committee as mediation.